Employee diversity and firm value of listed Nigerian consumer goods manufacturing companies - Kolawole, Joseph Seun; Alabi, Adeyemi Wasiu (International Journal of Emerging Trends in Social Sciences, 2024)
The persistent decline in the value of quoted consumer goods manufacturing companies in Nigeria from 2012 to 2021 served as the impetus for this study, which sought to explore the influence of employee diversity on the value of listed consumer goods manufacturing firms in the country. Specifically, the study investigated the impact of employee gender diversity, physical disability diversity, and race and cultural diversity on firm value. Employing ex-post facto methodology, the study centred on twenty-two consumer goods manufacturing firms listed on the Nigeria Exchange (NGX) as of December 31, 2021, representing both the population and sample. Data spanning from 2012 to 2021 were collected from the published reports of these firms and subjected to analysis, using descriptive statistics and panel regression. The findings revealed that employee gender diversity and physical disability diversity exerted significant positive effects on firm value, while the influence of employee race and cultural diversity was found to be insignificantly positive. As a result, the study concluded that the value of consumer goods manufacturing firms in Nigeria is influenced by employee diversity. To capitalize on these findings, the study recommended that such firms should embrace workforce diversity strategies and ensure transparent disclosure of employee information in their financial statements.